10.1001/jama.2012.5833.test (CrossRef Listing of Deleted DOIs, 2000)
Importance Lower estimated glomerular filtration rate (eGFR) is associated with increased rates of death and kidney and cardiovascular events. Associations of measured GFR (mGFR) with outcomes remain unclear. Objective To quantify associations between mGFR and adverse clinical outcomes and to compare these with eGFR-based associations. Design, setting, and participants Retrospective observational cohort study of 6174 adults from Stockholm, Sweden, between January 1, 2011, and December 31, 2021. Exposure Measured GFR was obtained based on plasma clearance of intravenously administered iohexol (primary independent variable of interest). Estimated GFR was calculated with plasma creatinine (eGFRcr), cystatin C (eGFRcys), or both (eGFRcr-cys), using the Chronic Kidney Disease Epidemiology Collaboration 2021 and 2012 equations. Main outcomes and measures Primary outcomes were all-cause mortality and kidney failure with replacement therapy. Associations of each GFR measure with outcomes were evaluated using hazard ratios adjusted for age, sex, body mass index (calculated as weight in kilograms divided by height in meters squared), medical history, medications, and urine albumin to creatinine ratio. Results Of 6174 participants (median age, 59 years [IQR, 43-69]; 3686 [60%] were male and 2488 [40%] were female), 1977 (32%) died and 426 (6.9%) developed kidney failure with replacement therapy during a median follow-up of 5.9 years (IQR, 3.0-8.8 years). Compared with a baseline mGFR of 90 mL/min/1.73 m2, an mGFR of 60 mL/min/1.73 m2 was associated with higher rates of all-cause mortality (27.6 vs 22.4 per 1000 person-years; hazard ratio [HR], 1.21; 95% CI, 1.14-1.28) and kidney failure with replacement therapy (1.2 vs 0.4 per 1000 person-years; HR, 2.85; 95% CI, 2.06-3.94). For all-cause mortality, associations for eGFRcr-cys did not significantly differ from those for mGFR (ratio of HRs [RHRs] at 60 mL/min/1.73 m2, 1.03; 95% CI, 0.96-1.10), whereas eGFRcr underestimated the mGFR-based association (RHR, 0.87; 95% CI, 0.79-0.95) and eGFRcys overestimated it (RHR, 1.17; 95% CI, 1.08-1.27). Conclusions and relevance Among adults in Sweden, mGFR values of 60 mL/min/1.73 m2 were associated with higher rates of all-cause mortality and kidney failure compared with mGFR values of 90 mL/min/1.73 m2, supporting the current GFR threshold of 60 mL/min/1.73 m2 to define chronic kidney disease. Associations of mGFR with mortality were most closely represented by the association of eGFRcr-cys with mortality, whereas eGFRcr underestimated and eGFRcys overestimated mortality risk.